Kawaii discourse: The semantics of a Japanese cultural keyword and its social elaboration - Asano-Cavanagh, Yuko (2017)
Providing new case studies, the volume showcases the diversity of ways in which cultural logics form and shape discourse. The Natural Semantic Metalanguage (NSM) approach is used as a unifying framework for the studies.